PENGARUH FAKTOR SOSIAL TERHADAP KEPUTUSAN WISATAWAN DOMESTIK DALAM MEMILIH HOTEL BERBINTANG DI KAWASAN WISATA SENGIGI PULAU LOMBOK - Suryantini, Suryantini (Master of Management, Mataram University, 2017)
This research is aimed at determining the effect of Reference Group, Family, Role and Status on the decision of Domestic Tourists in Choosing Tourist Hotel in Lombok.Â This research is quantitative causality study. The population of this research are customers of Sheraton Hotel and Killa Hotel. The samples were 100 respondents selected through purposive sampling. The data were analyzed with multiple linear regression using SPSS program.The research showed that reference group variable had positive and significant effect on the decision of domestic tourists in choosing Tourist hotel in Lombok, the family variable had positive and significant effect on the decision of domestic tourists in choosing Tourist hotel in Lombok, the role and status variable had positive and significant effect on the decision of domestic tourists in choosing Tourist hotel in Lombok.Â Keywords:Reference Group, Family, Role and Status, Decision of Domestic Tourists